Characteristics of aortic root and vascular anatomy in bicuspid versus tricuspid aortic valve anatomy. (14th October 2021) - Hamdan, A; Witberg, G; Perlman, G; Aviv, Y; Shiyovich, A; Vaknin Assa, H; Abid Assali, A; Lessick, J; Kerner, A; Segev, A; Barabash, I; Goitein, O; et al.
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is being increasingly performed in patients with bicuspid aortic valve stenosis (AS). Purpose: This study sought to compare aortic root, aorta and iliofemoral artery anatomy in patients with bicuspid versus tricuspid AS. Methods: 172 patients with bicuspid AS and 331 patients with tricuspid AS underwent pre-procedural computed tomography (CT) evaluation before TAVR. Dimensions, calcification, and tortuosity of the iliofemoral arteries were evaluated and the dimensions of aortic root, aorta, and left subclavian arteries were determined. Results: Dimensions of aortic root, aorta, left subclavian, and iliofemoral arteries were consistently and significantly larger in bicuspid than in tricuspid AS (P<0.001). Patients with bicuspid AS had significantly lower subclavian, aorta, and iliofemoral arteries calcification, lower tortuosity index and lower maximal tortuosity angle compared to patients with tricuspid AS (P<0.001 for all) even after adjustment for baseline characteristics (Figure). Compared to tricuspid AS the prevalence of porcelain aorta and aneurysm in the descending aorta and iliofemoral arteries were significantly less common in bicuspid valve anatomy. After adjustment for baseline characteristics Bicuspid valve anatomy was associated with lower odds of vascular calcification (odds ratio (OR) 0.82: 95% CI 0.52–0.93; P=0.001). Conclusions: Bicuspid AS was associated with larger dimensions of aortic root, aorta, subclavian, and iliofemoral arteries compared with tricuspid AS. Low vascular calcification and decreased tortuosity index of iliofemoral arteries characterized bicuspid anatomy. Further studies are needed to evaluate the impact of bicuspid vascular anatomy on vascular complications after TAVR. Funding Acknowledgement: Type of funding sources: None.